KETIMPANGAN DANA DAN PEMBIAYAAN DALAM NEGERI, HARUSKAH DIPENUHI DENGAN HUTANG LUAR NEGERI? - Edy Rahmantyo Tarsilohadi (Muhammadiyah University Press, 2005)
This research examined the effect of the foreign debt toward the development of Indonesian economy by using caucality test: Final Prediction Error.Examination of the data, indicates the causality linkage between the foreign debt and the gross domestic product, vice versa; the causality linkage between the foreign debt and the depreciation of the rupiah.This result indicates that the foreign debt was failed to push economic.